Integrating Digital Technologies in Visual Arts Education: Enhancing Creativity and Competencies - Kamolova E’zoza Iskandar qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article examines the role of digital technologies in modern visual arts education. Focusing on the integration of graphic software, 3D modeling, animation tools, and virtual platforms, the study highlights how these technologies enhance students’ creative thinking, artistic literacy, and practical competencies. Based on Shovdirov S. A.’s research, the paper explores innovative teaching strategies, project-based learning, and interdisciplinary approaches that transform art education into a dynamic, interactive, and student-centered process.